RESIKO GANGGUAN KESEHATAN PADA0MASAYARAKAT SEKITAR TEMPAT0PEMBUANGAN AKHIR (TPA) TALANGAGUNG KABUPATEN MALANG - Hasanah, Uswatun; Rahayu, Amy Septiamuna Pamuji; Rizal, Syaiful; Rusydi, M. Imron (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims to determine risks to public health in the Talangagung Landfill. This type of research is a quantitative descriptive study. The population in this study is the people who live and work in TPA Talangagung, Malang Regency. The instrument used in this study used a questionnaire that was distributed to the community around the landfill site. Data analysis using quantitative descriptive analysis by collecting data obtained from the community, and then describes the results of the data collected as is by using the percentage formula. From the analysis of the questionnaire data there are 40% of respiratory disorders, 20% of digestive disorders and 10% of skin disorders. TPA Talangagung Malang Regency in its implementation is in accordance with procedures set by the government in accordance with the Law, so that the impact caused by the Talanggung TPA has no odor and does not cause environmental damage.Â Keywords: health; landfills